EFEKTIFITAS PENDIDIKAN KESEHATAN TENTANG IMUNISASI TETANUS TOKSOID (TT) TERHADAP PENGETAHUAN IBU DI PMB FAUZIAH HATTA - Amallia, Siti; Anggraini, Helni; Rohmin, Anur; Indah Syafriani, Elvina (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
TThe infection of Tetanus is one of the causes of maternal and infant mortality. Death due to tetanus infection is the result of an unsterile delivery process or comes from wounds obtained by pregnant women before giving birth. In an effort to control tetanus infection, which is a risk factor for maternal and infant mortality, a Tetanus Toxoid Diphtheria vaccine is being implemented for Women of Childbearing Age and pregnan. The aim of this research was to determine the effectiveness of health education about Tetanus Toxoid (TT) Immunization on mothers' knowledge at PMB Fauziah Hatta. This research was a pre-experimental research with a one group pretest-posttest design. The sampling method used in this research was a purposive sampling technique. The sample in this research were women of childbearing age and pregnant, totaling 35 respondents. The research was carried out in June - October 2023 at PMB Fauziah Hatta, Palembang city. The research results showed that the average mother's knowledge score before being given health education was 55.06, the average mother's knowledge score after being given health education was 76.03. The results of statistical tests using the Paired T Test obtained ρ-value = 0.000, which means there were a difference in mothers' knowledge before and after being given health education about Tetanus Toxoid (TT) Immunization at PMB Fauziah Hatta in Palembang. It was recommended that health workers increase health education about Tetanus Toxoid (TT) Immunization which aims to build the immunity of mothers and babies from the toxin that causes tetanus.